1988
DOI: 10.1093/aepp/10.1.1
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Composite Forecasting Methods

Abstract: This paper assesses the potential benefits of composite forecasting methods as applied to commodity prices. Conditions under which composite forecasts are most applicable are examined. A Monte Carlo simulation and empirical examples are used to assess the benefits of composite forecasts and provide guidelines on the selection of appropriate methods. The importance of independent pieces of information and why composites cannot be a cure for poor forecasts under many realistic situations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Along the same lines Park and Tomek (1989) evaluated several forecast models (including ARIMA, VectorAutoregression and OLS for their variances) and concluded in favour of the composite approach. Combining several forecast models gave the lowest MSE when compared to the same models not being combined.…”
Section: Composite Forecast Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along the same lines Park and Tomek (1989) evaluated several forecast models (including ARIMA, VectorAutoregression and OLS for their variances) and concluded in favour of the composite approach. Combining several forecast models gave the lowest MSE when compared to the same models not being combined.…”
Section: Composite Forecast Modelsmentioning
confidence: 99%
“…Just to mention a few see for example, Engle (1982), Taylor (1985) Bollerslev et al (1992), , Susmel and Thompson (1997), Wei and Leuthold (1998), Engle (2000), Manfredo et al (2001). However, there is less evidence that ARCH models give reliable forecasts of commodity price volatility for out-of-sample evaluation (Park and Tomek, 1989, Schroeder et al, 1993, Manfredo et al, 2001. All of them found that the explanatory power of these out-of-sample forecasts is relatively low.…”
Section: Historical Volatility Modelsmentioning
confidence: 99%
“…(2001), among others. 7 However, the out-of-sample forecasting accuracy of these types of non-linear models could be, in some cases, questionable (see Park and Tomek: 1989, Schroeder et. al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2001). However, there is less evidence that ARCH models give reliable forecasts of commodity price volatility for out-of-sample evaluation (Park and Tomek: 1989, Schroeder et. al.…”
Section: Historical Volatility Modelsmentioning
confidence: 99%
“…They created the weights for the composite forecast model based upon the forecast ability of each individual model in terms of their Mean-Squared-Errors (MSE). Along the same lines Park and Tomek (1989) evaluated several forecast models (including ARIMA, Vector-Autoregression and OLS for their variances) and concluded in favour of the composite approach. Combining several forecast models gave the lowest MSE when compared to the same models not being combined.…”
Section: Composite Forecast Modelsmentioning
confidence: 99%